2020
DOI: 10.4018/978-1-7998-5074-8.ch005
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Personalized Online Learning System Towards Creating Hybrid Learning and Teaching in Chemistry Classes

Abstract: Recent technological advances have allowed for the use of computerized and online systems to achieve personalized student-centered learning and teaching in the classroom. One such prominent example is the PeTeL system (Personalized Teaching and Learning), developed by the Science Teaching Department of the Weizmann Institute of Science. In the present article, we describe the initial stages of the system's first implementation in chemistry classes, and show how it facilitates the hybridization of learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Moodle is extensively used worldwide, with over 212 million users ( stats.moodle.org ). The system’s Hebrew version is in broad use in Israel’s institutes of higher education and at the high-school level [ 69 ] since it addresses the needs of both administrators and educators [ 70 ]. Given the need that arose during the covid pandemic, the Moodle system was made available for use by all of the Institute’s lecturers starting in the 2021 academic year.…”
Section: Discussionmentioning
confidence: 99%
“…Moodle is extensively used worldwide, with over 212 million users ( stats.moodle.org ). The system’s Hebrew version is in broad use in Israel’s institutes of higher education and at the high-school level [ 69 ] since it addresses the needs of both administrators and educators [ 70 ]. Given the need that arose during the covid pandemic, the Moodle system was made available for use by all of the Institute’s lecturers starting in the 2021 academic year.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the pandemic, the PeTeL system was used for registering all the chemistry teachers in Israel. An example of one assignment regarding states of matter was described in Aviran et al 16 We demonstrated PeTeL in the chemistry teachers' PLC. The link to register to the system was uploaded to the website.…”
Section: Tutorials For Zoom In Hebrew Andmentioning
confidence: 86%